Insights into the regulation of C‐repeat binding factors in plant cold signaling. Issue 9 (18th July 2018) - Liu, Jingyan; Shi, Yiting; Yang, Shuhua
Abstract: Cold temperatures, a major abiotic stress, threaten the growth and development of plants, worldwide. To cope with this adverse environmental cue, plants from temperate climates have evolved an array of sophisticated mechanisms to acclimate to cold periods, increasing their ability to tolerate freezing stress. Over the last decade, significant progress has been made in determining the molecular mechanisms underpinning cold acclimation, including following the identification of several pivotal components, including candidates for cold sensors, protein kinases, and transcription factors. With these developments, we have a better understanding of the CBF‐dependent cold‐signaling pathway. In this review, we summarize recent progress made in elucidating the cold‐signaling pathways, especially the C‐repeat binding factor‐dependent pathway, and describe the regulatory function of the crucial components of plant cold signaling. We also discuss the unsolved questions that should be the focus of future work. Abstract : Cold acclimation is an effective mechanism to defense freezing tolerance for plants. CBF transcription factors play predominant roles in plant cold acclimation and tolerance. We summarize the biological function of the CBFs in cold acclimation, and the regulation of the CBF signaling pathway at both transcriptional and post‐translational level.